2001
DOI: 10.1055/s-0037-1616049
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and Factor V R2 Allele: High-throughput Analysis and Association with Venous Thromboembolism

Abstract: SummaryThrombophilia is a multigenic disease in which the combination of genetic polymorphisms increases the risk of deep vein thrombosis (DVT). The rapid identification of these genetic combinations requires high-throughput analysis of single nucleotide polymorphisms (SNPs). The TaqMan® fluorogenic 5’→3’ nuclease assay (PE/Applied Bio-systems, Foster City, CA) with custom-designed primers, probes and controls has provided a highly efficient platform for high throughput. This assay was used to rapidly detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Two differently labeled probes are used in genotyping, one specific for the mutant probe, and one for the normal probe. Fluorescence due to the different reporter dyes is typically measured after all PCR cycles have been completed [18].…”
Section: Methodsmentioning
confidence: 99%
“…Two differently labeled probes are used in genotyping, one specific for the mutant probe, and one for the normal probe. Fluorescence due to the different reporter dyes is typically measured after all PCR cycles have been completed [18].…”
Section: Methodsmentioning
confidence: 99%
“…Another study reported evidence to support an association of the FV A4070G polymorphism with deep venous thrombosis (DVT) . Some other studies, however, suggested that there were no statistical differences in the prevalence of this polymorphism between patient and control groups .…”
Section: Discussionmentioning
confidence: 85%
“…Studies varied greatly in the extent to which they described the population from which the participants came; only 17 studies adequately reported the setting or population from which the blood samples were obtained [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Most described the experimental test adequately; 60 to 70% of the studies gave a detailed description of their reference methods.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared Taqman 1 real-time polymerase chain reaction (PCR) to PCR-RFLP [17,32,41]. The concordance was 100% in all these studies.…”
Section: Detection Of Fvlmentioning
confidence: 99%